Optimal Bunching without Optimal Control - Georg Nöldeke; Larry Samuelson (University of Basel, Center of Business and Economics (WWZ), 2006)
This paper presents simple su±cient conditions under which optimal bunches in adverse-selection principal-agent problems can be characterized without using optimal control theory.
Keywords: C60; C70; D40; D80; 330; Principal-Agent Problem; Bunching; Nonlinear Pricing; Assignment Approach